Investigation of Dried Blood Spot Cards for Fatty Acid Analysis Using Porcine Blood - Jordan Wood; Larry J. Minter; Michael K. Stoskopf; Doug Bibus; Dempsy Ange; Troy N. Tollefson; Vivek Fellner; Kimberly Ange-van Heugten (Veterinary Medicine International)
Fatty acids, especially omega-3 and omega-6 fatty acids, are important for reproductive and cardiovascular health in animals. While monitoring fatty acids is traditionally conducted using frozen blood fractions such as serum and plasma, advancements in analytical technology have developed a method of collecting microsamples of dried whole blood on Ahlstrom 226 grade filter paper that can provide information on long-term fatty acid status of animals. Blood samples were collected from five male pigs in both the traditional frozen method and on dried blood spot cards (DBS). The DBS samples were collected with untreated syringes and tubes, and approximately 320 μL of blood was placed on each card with approximately 80 μL per spot (4 spots). Statistical analysis was performed to compare the two sample groups to each other using the Mann–Whitney U-test and determine if DBS samples were similar to traditional whole blood samples. Of the 30 fatty acids and fatty acid groups with measurable concentrations, only four individual fatty acids, behenic acid, omega-3 docosapentaenoic acid, nervonic acid, and adrenic acid, had statistical differences. Most of these differences were minor and could be due to analytical errors or contamination. Comparisons between sample types found similar concentrations of key omega fatty acids and PUFAs and support the use of DBS collection as a less invasive method of blood collection and fatty acid analysis.